The Highlander: The Art of Decolonising Publishing - Heneise, Michael (Septentrio Conference Series, 2020)
See RECORDING (starts at 01:13:30).In 2015, I embarked on a new project with my former PhD supervisor at Edinburgh: to create a respected area studies journal of Highland Asia that would be both accessible and accountable to the communities where, and with whom, we do our research: Highland Asia! We successfully built up an editorial board of renowned scholars, convinced the Edinburgh University Library to be our publisher, and soon we had our journal online, with a short first issue free to download anywhere. However, we suddenly realised that we had lost something in the process. While we now engage with the global academic community, offering excellent peer-review, and editorial value to authors, we also found we were beginning to replicate a publishing model we were trying to get away from. Like pay-wall journals we were operating in a space at a distance, closed off, and culturally inaccessible to the communities we were eager to engage with. Can Open Access forge new pathways that are different from the pay-wall journals and big publishers? In recent months, we have started to look at our old notes, to see where we might regain our footing, to get back that ‘anarchist’ DIY inspiration! Providing free downloadable PDFs is good, but it is no great achievement anymore. How can we meaningfully bridge the worlds we work in so that knowledge production itself is more open? In our case, we think one approach is to open up the entire publishing process. In addition to indigenous authors and reviewers, we want to engage proof-readers, copyeditors, typesetters, photographers, cover designers, printers and remote college departments and libraries across the Himalayas. We have only started exploring this in 2020, but in the process we have discovered that there is great demand, for example, for printed versions. Easily produced locally, we could set up a basic subscription model, and stock local college libraries, book stores, and coffee shops in Northeast India, Bhutan, Sikkim, and Nepal. By opening up, and engaging in dialogue with local scholars, librarians, designers, and artists we have found all kinds of opportunities that help our journal move in the direction of being truly ‘Open Access’ in every way. In Edinburgh, we have also found a community of PhD students doing research on the Himalayas, excited to learn about publishing. We are forming an editorial collective that is now connecting with our community in Asia, offering additional contacts that can facilitate research exchange. Our journal remains experimental. We have, for example, decided to go with a rolling publishing model instead of distinct issues. I also want to engage my own students in Tromsø, especially in editorial management. I also hope we can develop synergies with the Open Access community in Norway. Beyond library publishing, we see an opportunity to create a new space, instead of combatting an old space dominated by for-profit publishers. Finally, by crossing borders, and truly opening up in this way, we also push this idea of knowledge production towards greater accountability. Indeed we are calling for truly tangible ways in decolonising publishing.
Keywords: decolonising publishing; Open Access; Himalayas